1999
DOI: 10.1094/pdis.1999.83.7.633
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Isolates of Phytophthora infestans from Tomato and Potato in North Carolina from 1993 to 1995

Abstract: Eighty-five isolates of Phytophthora infestans from 33 tomato and 8 potato fields in North Carolina, South Carolina, and Tennessee were collected from 1993 to 1995 and tested for mating type, sensitivity to metalaxyl, and allozyme genotype at glucose-6-phosphate isomerase (Gpi) and peptidase (Pep) loci. One isolate collected from potato in eastern North Carolina in 1994 was the A1 mating type, whereas all other isolates from potato and tomato were the A2 mating type. Six isolates were sensitive to metalaxyl (&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 41 publications
4
18
0
1
Order By: Relevance
“…The fact that metalaxyl resistance was found also on untreated fields agrees very well with findings of other authors (Fraser et al 1999;Day et al 2004). Our own data suggest that a high rate of migration of resistant isolates into unsprayed fields took place, as reported previously by other authors (Fraser et al 1999).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The fact that metalaxyl resistance was found also on untreated fields agrees very well with findings of other authors (Fraser et al 1999;Day et al 2004). Our own data suggest that a high rate of migration of resistant isolates into unsprayed fields took place, as reported previously by other authors (Fraser et al 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Our own data suggest that a high rate of migration of resistant isolates into unsprayed fields took place, as reported previously by other authors (Fraser et al 1999). Fraser et al (1999) found that the frequency of metalaxyl-resistant isolates was not significantly greater in metalaxyl-sprayed than in unsprayed fields.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The P. infestans US-7 genotype was the predominant in the Columbia Basin of Washington and Oregon during 1993, and was highly pathogenic on tomatoes in addition to potatoes ). The P. infestans US-8 genotype was predominant in most other potato-growing areas of Canada and the United States since the mid-1990s and displaced all other genotypes (Fraser et al 1999;Fry and Goodwin 1997a). The P. infestans US-8 genotype was reported to have greater pathogenic fitness on the potato, with higher infection efficiency, sporulation capacity, and shorter latent period on potato foliage and tubers than other genotypes (Lambert and Currier 1997;Miller et al 1998).…”
Section: Evolution Of Late Blight Populations In United States and Camentioning
confidence: 99%
“…This was evident from the appearance, in the late 1970s, of metalaxyl-resistant isolates of P. infestans in European populations after only a few seasons of fungicide application (Dowley and O'Sullivan 1981). By 1993, the metalaxyl-resistant isolates of the US-7 and US-8 genotypes had displaced the metalaxyl-sensitive isolate of the US-6 genotype (Fraser et al 1999). The P. infestans US-7 genotype was the predominant in the Columbia Basin of Washington and Oregon during 1993, and was highly pathogenic on tomatoes in addition to potatoes ).…”
Section: Evolution Of Late Blight Populations In United States and Camentioning
confidence: 99%